Preclinical Modeling of DCD Class III Donation: Paving the Way for the Increased Use of This Challenging Donor Type. (3rd September 2019) - Soussi, David; Rod, Xavier; Thuillier, Raphael; Leblanc, Suzanne; Goujon, Jean-Michel; Barrou, Benoit; Hauet, Thierry; Kerforne, Thomas
Abstract : Deceased after circulatory death (DCD) donors offer a viable solution to the current organ shortage, particularly the Maastricht Class III (arrest subsequent to cessation of life support in the hospital). Although current results from these donors are very satisfactory, the number of included donors is too low and future expansion of inclusion criteria will likely decrease organ quality, with negative consequences on the complication rate. This donor type thus represents a priority in terms of scientific exploration, so as to study it in controlled settings and prepare for future challenges. Hence, we mimicked the DCD Class III clinical conditions a Large White pig model. Herein, we detail the different strategies attempted to attain our objectives, including technical approaches such as animal positioning and ventilator settings, as well as pharmacological intervention to modulate blood pressure and heart rate. We highlight the best combination of factors to successfully reproduce DCD Class III conditions, with perfusion pressures and functional warm ischemia (hypoperfusion) closely resembling clinical situations. Finally, we detail the functional and histological impacts of these conditions. Such a model could be of critical value to explore novel management alternative for these donors, presenting a uniquely adapted platform for such therapeutics as normothermic regional circulation and/or pharmacological intervention.